Membangun toleransi dengan ajaran al-qur’an dan hadits tentang kerukunan beragama - Syafinah, Ariyanti Kholidatus; Nidhom, M. Saifun; Aslam, Ahmad Riziq; Hasan, Nayla Royani; Awaliyah, Etik Nur; Sulistyowati, Anis Anggun (Maliki Interdisciplinary Journal, 2025)
Religious tolerance is the foundation used in the development of society in order to be harmonious and harmonious. Islam as the majority religion in Indonesia, explicitly instils the values of tolerance and togetherness among religious believers. The Qur’an and Hadis, as the core of islam, include many verses and hadis that emphasise the importance of peaceful coexistence with other religions. This article examines the theological basis of tolerance in islam. Throught an in-depth analysis of Qur’anic verses such as surah al-kafirun, surah al-baqarah verse 256 and other verses, as well as everything attributed to the Prophet Muhammad (SAW) related to tolerance, it will be explained how islam teaches Muslims to respect the beliefsof others. In addition, this article will also discuss important concepts in islam that support the realisation of tolerance, such as ukhuwah insaniyah (brotherhood among humans) andv adl (justice). By understanding the theological basis of tolerance in islam, it is hoped that Muslims can better implement the value of tolerance in individual and community life.